Critical moments? Life transitions and energy biographies. Issue 86 (November 2017) - Shirani, Fiona; Groves, Christopher; Parkhill, Karen; Butler, Catherine; Henwood, Karen; Pidgeon, Nick
Highlights: Linked lives is an important concept for understanding everyday energy use. QL design facilitates detailed exploration of life transitions and unfolding impacts over time. A critical moments lens overlooks small changes contributing to shifting energy use. There are challenges in seeing lifecourse changes as moments for intervention. Abstract: Family and youth research has highlighted the importance of lifecourse transitions, illustrating how they can have a substantial impact on people's everyday lives and anticipated futures. Given their apparent significance, it is surprising that relatively little attention has been paid to life transitions – particularly unexpected ones – to explore how they can impact upon everyday energy use. This is a central concern of Energy Biographies project. The project's qualitative longitudinal design makes an original contribution, affording a detailed view of how transitions unfold and their significance for energy demand and environmental action. Central to elucidating these issues is the concept of 'linked lives', recognising that people live interdependently. In this paper, we explore the accounts of three participants who experienced one or more life transitions during the course of the project, in order to consider the impacts of these events (both planned and unanticipated) on their everyday energy use and environmental actions as part of their linked lives with others.